COMPOST FERTILIZER DEVELOPMENT STRATEGY IN SUMBER BAKTI VILLAGE, DARUL MAKMUR DISTRICT, NAGAN RAYA DISTRICT - David Triansaf; Teuku Athaillah; Bagio; Noratun Juliaviani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
As an agricultural area, the agricultural sector is the dominant economic support in Nagan Raya Regency. The agricultural sector has very good prospects so that it is widely cultivated by the community, coupled with favorable land conditions. Darul Makmur District is one of the sub-districts in Nagan Raya Regency and is the largest sub-district with an area of ​​1,027.93 km2 with a distribution of 29.00%. The majority of the people make their living as farmers. This research aims to analyze the supporting factors for the development of compost fertilizer in Sumber Bakti Village. The primary data collection method was to conduct interviews with 30 respondents using a prepared questionnaire and information obtained from Focus Group Discussion (FGD). Data analysis in this study used the SWOT method and weighting using the Analytical Hierarchy Process (AHP). The research results show the highest score on internal factors (Strengths) Production costs are relatively cheap with a total score of 0.34 Internal Factors (Weaknesses) It takes a long time to make compost fertilizer with a total score of 0.55 External Factors (Opportunities) Demand for compost fertilizer is increasing 0.36 External Factors (Threats) Unpredictable weather hampers the production process with a total score of 0.64. Defensive strategy is the right strategy to implement. Some of these strategies are; Equipping production facilities and infrastructure so that the quality of raw materials is maintained and reducing production costs, as well as increasing the quantity and quality of compost production in accordance with Indonesian National Standards (SNI).